Optimization of Whole Blood Specimen Handling for Complete Blood Count (CBC) Results and Blood Cell Morphology - Andika Aliviameita; Puspitasari Puspitasari; Widya Intan Amilya; Igfina El Savitra (Jurnal Kesehatan, 2025)
Hematology analyzers are used in almost all clinical laboratories for CBC testing. CBC test results are crucial, as they play a significant role in establishing diagnoses and determining the appropriate therapy for patients. This study aims to analyze the effect of anticoagulant type, storage temperature, and delay time on the results of erythrocyte, leukocyte, and thrombocyte counts in whole blood samples. The study design employed was a laboratory experiment with a total of 64 samples, which were subjected to a combination of treatments involving anticoagulant type (Vacutainer and conventional), storage temperature (room temperature and refrigerator), and delay time for testing (0, 6, 12, and 24 hours). The examination was conducted using a hematology analyzer, and data analysis was performed using the Kruskal–Wallis test and the post hoc Mann–Whitney U test. The results showed that there was no significant effect of the three factors on the number of erythrocytes and leukocytes. However, the delay time significantly affected the platelet count (p=0.004), with significant differences observed between 6 hours and 24 hours, and between 12 hours and 24 hours. The delay in blood examination with K3EDTA and Na2EDTA affects the morphology of erythrocytes and leukocytes. Abnormal changes occur after 6, 12, and 24 hours of storage. The gold standard is a fresh whole blood sample collected in a K3EDTA vacutainer tube with the correct volume and analyzed within a maximum of 2 hours at room temperature.